2017
DOI: 10.1515/wps-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Youth Guarantee in Italy and the New Policy Design Approach: Expectations, Hopes and Delusions

Abstract: The article presents an empirical analysis of the Italian Youth Guarantee (YG) based on the approach of the new policy design. After having reviewed the most recent literature concerning this analytical approach, it examines the rationales, actors, aims, and contextual factors, as well as the political dynamics, that characterised the design of the YG national plan and its first implementation at the local level. The article argues that the Youth Guarantee offered the opportunity to think about the reorganisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In Italy, a study of such thriving regions such as Emilia-Romagna, Lombardy and Veneto found job centres void of a clear direction and short of enough resources. The authors concluded that the problem was common to most regions, but remarkably highlighted that these three regional governments had not been capable to overcome the problem since the Great Recession (Vesan & Lizzi, 2017). In addition, although the YGS officially targeted the youth between 18 and 24, in practice many programmes enlisted youth up to 29.…”
Section: Discussion Of Results Through a Literature Review Of Relevan...mentioning
confidence: 99%
“…In Italy, a study of such thriving regions such as Emilia-Romagna, Lombardy and Veneto found job centres void of a clear direction and short of enough resources. The authors concluded that the problem was common to most regions, but remarkably highlighted that these three regional governments had not been capable to overcome the problem since the Great Recession (Vesan & Lizzi, 2017). In addition, although the YGS officially targeted the youth between 18 and 24, in practice many programmes enlisted youth up to 29.…”
Section: Discussion Of Results Through a Literature Review Of Relevan...mentioning
confidence: 99%
“…Second, there is a focus on specific initiatives in the EPSR, with a growing interest in specific soft programmes, including (co-)funding initiatives such as the Youth Guarantee (Vesan & Lizzi, 2017;Tosun et al, 2019;, and the Fund for the Most Deprived (Madama, 2016;Greiss et al, 2021).…”
Section: The Current State Of the Debate And The Covid-19 Pandemic: A...mentioning
confidence: 99%
“…Second, there is a focus on specific initiatives in the EPSR, with a growing interest in specific soft programmes, including (co-)funding initiatives such as the Youth Guarantee (Vesan & Lizzi, 2017;Tosun et al, 2019;, and the Fund for the Most Deprived (Madama, 2016;.…”
Section: The Current State Of the Debate And The Covid-19 Pandemic: A...mentioning
confidence: 99%